Cyber-attack and Measuring its Risk - Sheleme, Mihret; Sharma, R. Rajesh (IRO Journal on Sustainable Wireless Systems, 2021)
In this short research, cyber-attack and the well-known attacking methods are discussed. Moreover, how many attacks were made in 2021 compared to the attacks in the previous year is found, to determine how fast this malicious activity is growing and the reasons which motivate such cyber-attacks are studied. The risk measurement methods are also discussed in this article based on some previous research. The conclusions are made on the suitable solution for cyber-attack, reviewed based on the point of view of different research.